The Smell of War : Three Americans in the Trenches of World War I. - Bernhard, Virginia, 1937- (C.A. Brannen series., 2017)
"The war has a smell that clings to everything military, fills the troop-trains, hospitals, and cantonments, and saturates one's own clothing, a smell compounded of horse, chemicals, sweat, mud, dirt, and human beings."--Henry Sheahan. The smell of War opens with these evocative words, penned just over a century ago by an ambulance driver in the Great War. Historian Virginia Bernhard has deftly woven together the memoirs and letters of three American soldiers--Henry Sheahan, Mike Hogg, and George Wythe--to capture a vivid, poignant portrayal of what it was like to be "over there." These firsthand recollections focus the lens of history onto one small corner of the war, into one small battlefield, and in doing so they reveal new perspectives on the horrors of trench warfare, life in training camps, transportation and the impact of technology, and the post-armistice American army of occupation. Henry Sheahan's memoir, A Volunteer Poilu, was first published in 1916. It portrays the experiences of a Boston-born, Harvard-educated ambulance driver for the French army who later became a well-known New England nature writer, taking a family name "Beston" as his surname. George Wythe, from Weatherford, Texas, was a descendant of the George Wythe who signed the Declaration of Independence. He rose to the rank of major and later wrote the official history of the US Army's 90th Division. Mike Hogg, born in Tyler, Texas, was the son of former Texas governor James Stephen Hogg. He commanded troops from the trenches and wrote letters home, most of them to his sister, Ima. The Smell of War, by collecting and annotating the words of these three individuals, paints a new and revealing literary portrait of the Great War and those who served in it. --